Assessment of Insulin and Cortisol Levels in Iraqi Women with Breast Cancer - Shahad Adel Jarallah; Falah S. Al-Fartusie; Dheaa Shamikh Zageer (Al-Mustansiriyah Journal of Science)
Hormones are thought to primarily influence cancer risk by regulating the pace of cell division, cell differentiation, and the amount of cancer-vulnerable cells. Higher insulin levels and cortisol have been linked to some cancers, including breast cancer. Here, we evaluated the relationship between insulin and cortisol signaling and cancer, as well as the effect of these two hormones on organs, subcellular elements, and the process of carcinogenesis. We also consider the time points to prevent and cure breast cancer in insulin signaling. The ultimate objective is to enhance general health. Insulin and cortisol levels were tested and the results showed much higher insulin levels in breast cancer patients compared with control (p<0.001), whereas cortisol levels tested were lower in breast cancer patients compared with control with no statistically significant changes (p>0.05).